Perancangan Dokumentasi Sistem Manajemen pada Laboratorium Mekatronika UNS Berdasarkan SNI ISO/IEC 17025 : 2008 - Aditha Capryani; Fakhrina Fahma; Adrian Nur (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
This research designed of documentation management system laboratory for Mechatronics Laboratory based on SNI ISO/IEC 17025:2008 refers to documentation management system laboratory in UPT Integrated Laboratory. Mechatronics laboratory is expanding the scope of the UPT Integrated Laboratory. Design of documentation management system laboratory required to obtain accreditation from KAN. Documents were designed consisting of level 1 Quality Guidelines, level 2 Procedures, level 3 Work Instrictions, and level 4 Forms. Design of the documents were done with five stages document requirements identification, business process identification, analysis the availability of the necessary documents, designing documents, and documents verification. From the stages, are known that 10 documents level 1 need adjustments, 2 documents level 3 and 11 documents level 4 need to be designed. On documents verification, it is known that there are documents that requires improvements in the format and content. If Mechatronics Laboratory develop, then required adjustments to the documents